(untitled) (Advances in Systems Science and Applications, 2021)
Patent Landscape Reports (PLR) have long been used in business, science and R&D. They enable data-driven decision making and minimizing the risks of strategic technology choices. The authors analyzed the patent landscape for 5G wireless communications using the PatentSight® software product. Among the companies, the clear leader by the Patent Portfolio Index is Samsung Electronics; among countries, it is USA and China. However, patents of high technological relevance and/or commercial value may appear in small tech companies, or as a “by-product” of other corporate activities. The research results are of interest to researchers and practitioners involved in the development and implementation of 5G technologies.